The burying place - Freeman, Brian, 1963- (Freeman, Brian, 1963- Jonathan Stride novel., 2010)
In the quiet town of Grand Rapids, Minnesota, a baby vanishes from her bedroom in an opulent lakeside home. Was she abducted, or does her father have a terrible secret to hide? That same night, a young policewoman gets lost in the fog and stumbles into the middle of a horrific crime. Now a sadistic killer wants her to play his deadly game.